2000
DOI: 10.1038/sj.ijo.0801355
|View full text |Cite
|
Sign up to set email alerts
|

Critical value for the index of body fat distribution based on waist and hip circumferences and stature in obese girls

Abstract: OBJECTIVE: To determine the critical value for the standard deviation score (SDS) of waist ± hip ratio (WHR)aheight (Ht), as an age-adjusted measure of body fat distribution, in relation to occurrence of biochemical complications in obese girls. DESIGN: Cross-sectional, clinical study. The (WHRaHt)-SDS was calculated as described previously. Obese girls were classi®ed into two groups according to the occurrence of abnormal values in either serum triglyceride, alanine aminotransferase or insulin level. The crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…In this dataset, children with a WC ≥71 cm were 14 times more likely to have a negative risk profile than normal ones [13]. In obese girls, Asayama et al have found the value of 77 cm for the WC to show the best combination of sensitivity and specificity to detect metabolic abnormalities in 120 subjects aged 9-15 years [2]. Due to the lack of published critical values for fat distribution in children and adolescents, based on measured biological endpoints, national representative centile distribution is useful in clinical settings.…”
Section: Discussionmentioning
confidence: 93%
“…In this dataset, children with a WC ≥71 cm were 14 times more likely to have a negative risk profile than normal ones [13]. In obese girls, Asayama et al have found the value of 77 cm for the WC to show the best combination of sensitivity and specificity to detect metabolic abnormalities in 120 subjects aged 9-15 years [2]. Due to the lack of published critical values for fat distribution in children and adolescents, based on measured biological endpoints, national representative centile distribution is useful in clinical settings.…”
Section: Discussionmentioning
confidence: 93%
“…In other studies, it was found that girls had almost 50% greater skinfold thickness than boys at all ages 25,31 and the percentage body fat was lower in obese boys than in obese girls. 28 In a study carried out on shantytown children from Sao Paulo, Brazil, the authors found that low energy expenditure may be a risk factor for weight gain in susceptible populations, this indicates that low energy expenditure may help to explain the increased risk of excess weight gain leading to obesity among shantytown girls compared with shantytown boys. 32 …”
Section: Anthropometric Statusmentioning
confidence: 99%
“…Abdominal visceral fat has recently been measured in children. [27][28][29][30] These studies have suggested that deleterious effects of visceral adipose tissue on blood lipid risk factors seen in adults are already present in children. Predicting visceral fat from anthropometric measures such as WC, WHR and sagittal diameter has been attempted in both adults and children.…”
Section: Anthropometric Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Waist circumference (WC) and hip circumference (HC) are the two basic anthropometric measurements taken and WC is divided by HC in order to create the waist hip ratio (WHR). Both WC and WHR provide an indication of abdominal obesity (Doll et al 2002;Ho et al 2001;Assayama et al 2000;Lev-Ran 2001;Lean et al 1995).…”
mentioning
confidence: 99%